Perceptions of students, professors and veterinarians about the teaching of Preventive Veterinary Medicine and Public Health (Revista de Ciências Agroveterinárias, 2008)
This study aimed to discuss the teaching of Preventive Veterinary Medicine and Public Health, according to the perceptions of students, professors and veterinarian doctors. The theoretical framework follows L.Fleck’s ideas, by establishing a relation between his epistemological category of “thought style” and the fields of practical activities related to the medical veterinary profession. Semi-structured interviews were performed with students and professors of Santa Catarina State Veterinary Medical School in order to identify their perceptions regarding to Preventive Veterinary Medicine and Public Health. The results indicate that the conceptions of social and preventive nature have little prominence in the course and that the thought style of Preventive Veterinary Medicine and Public Health is little emphasized, when compared to the other styles present in the profession. It is suggested that all thought styles should receive balanced emphasis in medical veterinary education. In addition to that, more encouragement towards interdisciplinary thought could be instrumental to help students to acknowledge the importance of all areas in their professional life. For the field of Preventive Veterinary Medicine and Public Health, it is recommended a teaching plan focusing on the acquisition of knowledge and experiences of learning that can assist students in solving health problems of community nature.
Keywords: veterinary education; Preventive Veterinary Medicine; Public Health.